The Effect of Current Ratio and Debt to Equity Ratio on Return on Assets at PT Aneka Tambang Tbk Period 2011-2020 - Endang Nurita (Journal of Research in Business, Economics, and Education, 2022)
The purpose of this study is to determine the current ratio and debt to equity ratio to return on assets at PT Aneka Tambang Tbk. The data collection method used is the documentation technique. The research subject used is the financial statements of PT Aneka Tambang Tbk for the period 2011 - 2020. The object of research used is the return on assets of PT Aneka Tambang Tbk. The statistical method in this study uses the EViews 11 program. The analytical techniques used are Descriptive Analysis Test, Classical Assumption Test (Multicollinearity Test, Heteroscedasticity Test, Auto Correlation Test and Normality Test), and Hypothesis Testing (Partial Test, Stimulant Test and Coefficient of Determination Test). ). The results showed that partially current ratio has a negative and insignificant effect on return on assets with t count (0.040083) smaller than t table (1.85955) and probability value (0.6458) greater than (0.05). While partially debt to equity ratio has a positive and significant effect on return on assets with a t-count value (3.204127) greater than r table (1.85955) and probability (0.0150) less than (0.05). Stimulatingly, the current ratio and debt to equity ratio have an effect on return on assets with the calculated f value (5.370354) greater than f table (4.06618) and probability (0.038587) less than (0.05). The contribution of the current ratio and debt to equity ratio to return on assets is 60.54%.